MODERN TENDENCIES IN THE FIELD OF THE COMMERCIAL REAL ESTATE MANAGEMENT IN UKRAINE - L.Chubuk (Vìsnik. Kiïvsʹkogo Nacìonalʹnogo Unìversitetu ìmenì Tarasa Ševčenka. Ekonomìka, 2014)
The advantages of owners, got from the use of services of professional real estate management, are exposed. The spheres of most distribution of professional services of real estate management, their progress trends, prevailing form of organization of mutual relations between the owner of the real estate and managing company, special terms of payments for services are revealed. The range of management services and specific criteria of a choice of management companies in domestic practice are exposed, the rating of the leading companies in the market of complex services of commercial real estate management in Ukraine is given. Dynamics of the indicators, characterizing a condition of the market and efficiency of using of commercial real estate in Kiev for the period before and after financial and economic crisis, is illustrated. Reasons that limits possibilities of strategic real estate management in a long-term prospect are examines. The comparative analysis of attractiveness of basic sectors of the Ukrainian commercial property market (office, trade, ware-house real estate) is conducted from positions of investing and professional management. There is proved that perspective of investments in the ware-house (industrial) real estate is reasonable.